Trend Analysis of Relative Sea Level Changes in the Aegean Sea with Copula Functions - Ahmet Yavuzdoğan; Emine Tanır Kayıkçı (Doğal Afetler ve Çevre Dergisi)
Nowadays, it is known that for many reasons such as climate change, the sea level has globally increased. Sea level rises affect coastal ecosystems and threaten coastal settlements. From a geodetic point of view, long term sea level observations are important in terms of determining the datum of vertical control networks. Copula functions, which are frequently used in many fields such as statistics, economics, actuarial analysis, meteorology and hydrology, have a correlation structure that reflects linear and nonlinear relationships and can show local dependencies. In this study, relative sea level changes in the Aegean Sea and the relationship of these changes with sea surface temperature were investigated by using a Copula based trend analysis method. The sea level data used in the study were obtained from 5 tide – gauge stations in the Aegean Sea. Copula based trend analysis was performed in sea level and sea surface temperature time series. The usability of Copula based trend analysis was investigated by comparing it with regression models. As a result, it was observed that although the relative sea level increased rapidly in the Aegean Sea between 1990 and 1998, it decreased between 1999 and 2008. Thanks to the Copula-based trend analysis applied in the sea surface temperature time series, it was observed that the relative sea level rise was caused by the increase in sea surface temperatures between 1990 and 1998. It was determined that sea level decreases between 1999 and 2008 were caused by the decrease in sea surface temperatures.